Multi-stressor Extremes Found on a Tropical Coral Reef Impair Performance - Lucey, Noelle; Haskett, Eileen; Collin, Rachel (Frontiers in Marine Science, 2020)
Global change has resulted in oceans that are warmer, more acidic and lower in oxygen. Individually any one of these stressors can have numerous negative impacts on marine organisms, and in combination they are likely to be particularly detrimental. Understanding the interactions between these factors is important as they often covary, with warming promoting hypoxia, and hypoxia co-occurring with acidification. Few studies have examined how all three factors interact to affect organismal performance, and information is particularly sparse for tropical organisms. Here we documented a strong relationship between high temperatures, low dissolved oxygen (DO), and low pH in and around a tropical bay. We used these field values to inform two multi-stressor experiments. Each experimental factor had 2 levels, one representing current average conditions and the other representing current extreme conditions experienced in the area. We used sea urchin righting response as a measure of organismal performance for an important reef herbivore. In the first experiment 2-hour exposures to a fully factorial combination of temperature, DO, and pH showed that righting success was significantly depressed under low oxygen. To more fully understand the impacts of pH, we acclimated sea urchins to control and low pH for 7 days and subsequently exposed them to the same experimental conditions. Sea urchins acclimated to control pH had significantly reduced righting success compared to animals acclimated to low pH, and righting success was significantly depressed under hypoxia and high temperature, compared to normoxia and ambient temperature. These results show that short, 2h exposures to the temperature and DO extremes that are already experienced periodically by these animals have measurable detrimental effects on their performance. The positive impact of reduced pH is evident only over longer, 7d durations, which are not currently experienced in this area.